The social network X as a channel for podcast dissemination: An Analysis of the Leading Audio Distribution Platforms - Martin Nieto, Rebeca; Díaz Lucena, Antonio (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2024)
Digital current affairs are characterised by the prominence of sound content. This investigation addresses the relationship between audio platforms and social networks, focusing on communication and interaction through X (Twitter). The link between networks and audio is scarcely researched despite the popularity of podcasts, especially among young audiences who are, at the same time, large consumers of social networks. Therefore, this paper aims to explore the opportunities offered by networks for the dissemination of audio content and the possible attraction of a significant potential audience. The relevance of social networks as meeting places for listeners is growing, mainly because they create dynamic communities and encourage interactivity. In this context, the goal is to find out how the main audio creation and distribution platforms in Spain use X to advertise their content and connect with their audience with a quantitative methodological approach, supported by a large sample (33,584 tweets). It is concluded that audio platforms that take advantage of the possibilities of the social network, coincide with content linked to entertainment and conversational genres. In addition, the results show that this specific content generate greater audience engagement and participation.